The Transformation of Rebana Al Ashfiya in Jurang Hamlet 1998-2020: Transformasi Rebana Al Ashfiya di Dusun Jurang Tahun 1998-2020 - Hermawan, Zara Sevira (Journal of Islamic History, 2023)
This study explains how the Rebana Art Transformation. Al ashfiya in Jurang Hamlet 1998-2020. The author gives the boundaries of the problem on three things, namely: (1) what is the historical background for the establishment of the Rebana Al Ashfiya Art? (2) What is the phase of the influence of local music art on Rebana Al Ashfiya Art in 1998-2013? (3) How is the new enthusiasm for Al Ashfiya Tambourine methods. The stages in this research are: (1) Heuristics is to find the necessary sources, both written and oral sources. (2) Source criticism of internal and external verification, (3) Interpretation or interpretation, (4) Historiography or historical writing. The results of this study are that the Rebana Al Ashfiya Art succeeded in bringing change in increasing the religious activites of the Dusun Jurang community through Islamic da’wah which was spread packaged in the from of music.